(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The development of social responsibility of future engineers, who must be able to predict and evaluate the results of their professional activities is a relevant aspect of training specialists at a technical university. The problem is becoming increasingly acute due to the rapid penetration of artificial intelligence into many areas of the socio-economic life of society, in which many researchers and entrepreneurs see not only benefits for mankind, but also threats due to fears of artificial intelligence getting out of human control. Although there are some disciplines at Ukrainian universities that in varying degrees deal with ethical issues of engineering, many higher schools do not typically consider professional ethics as a compulsory course, so it seems necessary to look for additional methods and techniques for the formation of engineering ethics and social responsibility as its key element in various types of activities. In 2021–2023, a pedagogical experiment was conducted at Kharkiv National Automobile and Highway University with the aim of selecting and testing a set of methods for developing future engineers’ social responsibility. To this end, an experimental group was formed from students of different specialities (122 students), in which a variety of pedagogical methods were used while studying various disciplines in the format of formal education (discussions, debates, solving dilemmas, projects, case studies, simulations, etc.), informal (round tables, conferences, contests, publishing results of research), and informal education (volunteering, involvement in civil activities), and a control group (120 people), in which these methods were not used. The following criteria and indicators for assessing the level of development of social responsibility were chosen: 1) a value-based criterion (awareness of social responsibility as a key feature of an engineer’s professionalism; 2) pragmatic (skills to navigate in a variety of professional situations and make responsible decisions); 3) reflective (ability to make evaluative judgments, self-esteem). In the study, we applied a mixture of quantitative and qualitative methods to evaluate the results of the experimental work by the chosen criteria and indicators. The positive impact of the tried-and-tested methods on the development of social responsibility in the next generation of engineers was experimentally proved. Promising for further scientific research is the improvement of pedagogical support of ethical skills’ formation in technical specialists, as well as a set of methods for diagnosing the socially significant characteristics of technical students.